Peripheral Artery Disease Accompanied by IntermittentClaudication in Rural Areas of Sikka Regency – A Cross SectionalStudy with Pulse Palpation Methods and Its Risk Factors - Sofian, Naldo; Prasetyo, Garry; Wibisono, Stephanie (UI Scholars Hub, 2017)
Introduction. There are few studies regarding peripheral artery disease (PAD by intermittent claudication) on adults in Indonesia, including its risk factors. This study aims to determine relationship and comparison of PAD accompanied by intermittent intermittent claudication risk factors in adult, especially in rural areas of Sikka regency, Flores, measured by pulse palpation. Methods. A cross sectional study in 3 primary healthcare working areas in Sikka regency and consecutive sampling had been done. Interview of risk factors was conducted and blood pressure was taken from all four extremities in supine position. Ankle brachial index (ABI) value was defined as systolic blood pressure of foot arteries (dorsalis pedis and posterior tibia) divided by highest systolic blood pressure among brachial artery. PAD was then defined by presence of both intermittent claudication and ABI <0.9. Random blood glucose, total cholesterol, and uric acid had been measured using EasytouchTM while urine examination was done using urine dipsticks. Results. A total of 333 subjects had been participated in which woman (64.9%), farmers (71.2%), working, less-than-5-yearhypertension history (30.3%) and mean age 57.47 years old were our majority subjects’ characteristics. There were 135 subjects had intermittent claudication and 39 (28.89%) of them had PAD. Several independent significant (p<0.05) risk factors include sex (man vs. female; p=0.001; OR 0.167 [0.056–0.497]) and proteinuria (p=.000; OR 6.612 [2.725–16.045]). Conclusion. Proteinuria and sex are independent risk factors and significantly related on PAD accompanied by intermittent claudication in adult of rural areas in Sikka regency.